A review of neuroendocrine immune system abnormalities in IBS based on the brain–gut axis and research progress of acupuncture intervention - Sun, Zhangyin; Wang, Xuejiao; Feng, Shangsheng; Xie, Chaoju; Xing, Yu; Guo, Liang; Zhao, Jingyu; Ji, Changchun (Frontiers in Neuroscience, 2023)
Irritable bowel syndrome (IBS) is a common digestive disorder in clinic. Current studies suggest that the pathogenesis of the disease is closely related to abnormal brain-gut interactions, hypokinesia, and visceral sensory hypersensitivity in the gastrointestinal tract and alterations in the intestinal microenvironment. However, it is difficult for a single factor to explain the heterogeneity of symptoms. The Rome IV criteria emphasized the holistic biologic-psycho-social model of IBS, suggesting that symptoms of the disease are closely related to neurogastroenterology and various abnormalities in brain-gut interaction. This paper comprehensively reviewed the relationship between brain-gut axis and IBS, the structure of brain-gut axis and the relationship between brain-gut axis and intestinal microenvironment, and discussed the relationship between the abnormal regulation of nervous system, endocrine system and immune system and the incidence of IBS on the basis of brain-gut axis. In terms of treatment, acupuncture therapy can regulate the neuro-endocrine-immune system of the body and improve the intestinal microenvironment, and it has the advantages of safety, economy and effectiveness. This paper studies the pathogenesis of IBS from local to global, micro to macro, and reviews the use of acupuncture to treat the disease as a whole, so as to provide new ideas for the treatment of the disease.